Comparison of Efficacy and Safety of Oral Use of Terbinafine and Itraconazole for the treatment of Tinea paedis: A Randomized Controlled Parallel Group Open Labeled Trial with Clinico-Mycological Correlation (Community Based Medical Journal, 2023)
Treatment of tinea paedis is very crucial with the different antifungal drugs. The purpose of the present study was to compare the efficacy and safety of oral use of terbinafine and itraconazole for the treatment of tinea paedis. This study was a double-blind, randomized, single-center clinical trial. The patients were randomly allocated to receive a daily dose of terbinafine 500 mg daily for 4 weeks (Group I) or 200 mg of itraconazole for 4 weeks daily (Group II). The primary efficacy criterion was mycological cure, defined as negative results on microscopy and culture at the end of follow-up and no requirement of second intervention treatment. Secondary efficacy criteria included clinical cure without second intervention treatment and mycological and clinical relapse rates. A total of 50 patients were included in this study, it was observed that majority patients were age belonged to 31-40 years in both groups. Regarding gender distribution of the study patients, it was observed that male were predominant in both groups, which was 20(80.0%) in group A and 19(76.0%) in group B. All hyperkeratotic patients were shown 100.0% cases of clinical response. However, interdigital lesion were recovered in 7(100.0%) cases in group A and 6(85.7%) cases in group B. In conclusion, tinea paedis is significantly improved by both drugs, without significant difference after 8 weeks follow-up.CBMJ 2023 July: vol. 12 no. 02 P: 150-156